Vulnerability of the HIV cascade of care in an Amazonian town: A qualitative study - Flavia Divino; Flavia Divino; Mathieu Nacher; Mathieu Nacher; Rafael dos Santos Pereira; Paulo Peiter (Frontiers Media S.A., 2023)
The HIV care cascade spans from diagnosis to patient linkage and retention in health services for treatment. Brazil has made substantial efforts to optimize the cascade of care. However, despite these advances, there are striking regional differences and difficulties from testing to treatment, particularly in the north and northeast regions, often reflecting social inequalities. Oiapoque, a highly affected city in the state of Amapá, shares its borders with an overseas European territory-French Guiana. The objective of this study was to get a clearer picture of the different components of the HIV care cascade in the municipality of Oiapoque. The study was exploratory and qualitative, involving the mapping of health structures in the research area and interviews with the responsible healthcare professionals working in the municipality. Patients are vulnerable at several levels, including mobility limitations, mismatched information that affects the linkage and retention of treatment, an absence of infectious disease doctors, an absence of user autonomy, missed appointments, dropouts, and abandonment of care. We found that the five recommended steps in the continuum of care for people living with HIV all had weak points or were non-existent or unavailable. These results will be fundamental to rethink the municipality's actions and the strategies of the Unified Health System SUS for the HIV epidemic in these border regions of the Amazon.